Yet Another Look at the Low Level Liquidity Trap - Meltzer, Allan H. (Econometrica, 1963)
PROFESSOR EISNER'S attempt to revive the liquidity takes the form of five objections to the findings reported by Bronfenbrenner and Mayer.2 In this note I will direct my discussion to the question of evidence for the trap and comment only briefly on other points which Eisner raises. The main burden of my argument is that evidence for or against the liquidity must rest on a demand function for money which explains more than the period surrounding the supposed trap. The post-1 920 data alone are inadequate to support (or reject) the hypothesis. For it has long been known that long-term bond yields peaked in the U.S. in 1920-21 and thereafter declined. A similar movement is shown by velocity. At issue are two questions: (1) whether the data for the 1930's and 1940's show a movement of two variables which are related or a co-movement of two variables each of which declined for any one of a number of other reasons,3 and (2) if the variables are related, do they show evidence of a trap?